Species of the type section of Sphagnum (Bryophyta, Sphagnaceae) in Poland - Melosik, Iwona (Biodiversity: Research and Conservation, 2006)
The paper presents data on the distribution and phytosociological preferences of species belonging to the genus Sphagnum, section Sphagnum, in Poland. The distribution maps were constructed on the basis of verified herbarium materials accessible in Polish and some German herbaria. All data were presented on the maps by using a cartogram technique in accordance with the ATMOS system. In Poland, S. palustre and S. magellanicum are the most common, widespread species, whereas S. centrale and S. affine are the rarest. S. centrale is found mainly in the eastern part of the country, influenced by the continental climate. Its characteristic distribution in Poland is indicative of its specific status. S. affine is more frequent in the northwestern part, in regions subjected to Atlantic climatic influences. S. papillosum is more scattered but the majority of its localities are in western Poland. So far, S. austinii has not been reported from any Polish locality. There are two regions with particularly high numbers of localities of the studied species: Pomerania (northwestern part of Poland) and the southern uplands.